Prediction of the Viscoelastic Behavior of Low‐Density Polyethylene Produced in High‐Pressure Tubular Reactors. Issue 3 (16th April 2015) - Pladis, Prokopios; Meimaroglou, Dimitrios; Kiparissides, Costas; Pinto, José Carlos
<x xml:space="preserve">Abstract</x> In the open literature, there is a lack of comprehensive predictive models that can provide detailed information on the distributed molecular properties of LDPE (e.g bivariate molecular weight‐long‐chain distribution, seniority–priority long‐chain branching distributions, etc.) produced in a high‐pressure process. To address this problem, Meimaroglou and Kiparissides (2010) developed a novel kinetic–molecular topology Monte Carlo (MC) algorithm to predict the exact molecular architecture of nonlinear polyethylene chains. In the present paper, the molecular information obtained from the kinetic–topology MC algorithm is introduced into a comprehensive rheological model, the so‐called "branch on branch" model of Das et al. (2006), to predict the rheological behavior of the LDPE melt in a high‐pressure ethylene polymerization tubular reactor. The model uses an ensemble of branched polymer chains generated by the kinetic–chain topology MC algorithm to calculate several important viscoelastic properties, including the viscosity–shear rate curve, the storage and loss moduli, etc. The predictive capabilities of the new proposed computational approach, combining the solutions of kinetic, chain topology, and rheology models, are fully assessed via a direct comparison of model predictions with available experimental measurements on the molecular weight distribution, long‐chain branching, and linear viscoelastic properties of two LDPE grades produced in industrial‐scale reactors.<inline-graphic xlink:href="ark:/27927/pgj111fjmtv" content-type="mren201500008-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />